Meningkatkan Pengenalan Huruf melalui Penggunaan Metode Bermain Kartu Huruf pada Anak Kelas 1 SD AL Hilal Kellu: Improving Letter Recognition through the Use of Letter Card Playing Method in Grade 1 Children SD AL Hilal Kellu - Mirdayati Aihena; Samsul Sahuad Semarang (ITScience (Information Technology and Science), 2024)
Recognizing letters is a fundamental aspect of early literacy learning, but many early-grade students still have difficulty recognizing letter symbols and connecting them to words; this shows that the current teaching methods have not provided optimal results in developing early literacy. This study aims to improve the ability to recognize letters of grade 1 students of SD AL Hilal Kellu through the letter card game method. This study uses the classroom action research (CAR) method in two cycles: planning, implementation, observation, and reflection. The study's results showed a significant increase in students' ability to recognize letters. In the Pre-Cycle, students' abilities only reached 48% (less category). After implementing the letter card game in Cycle I, students' abilities increased by 28% to 76% (sufficient category). The increase continued in Cycle II with an increase of 10%, so the average student achievement reached 86% (good category). This study concludes that the letter card game method effectively improves the ability to recognize letters while motivating students to learn actively. This approach creates an interactive and enjoyable learning atmosphere, making it suitable for use as a medium for early literacy learning. These findings provide a practical contribution to developing learning methods in elementary school environments, especially in conditions with limited resources.